Bacterial community in a freshwater pond responding to the presence of perfluorooctanoic acid (PFOA) - Zhang, Dongqing (Environmental technology, 2020)
Microbial community is an essential component of freshwater, providing valuable self-purification ecosystem service. Poly-and perfluoroalkyl substances (PFAS) have attracted increasing concerns in light of their potential ecotoxicological effects and ubiquitous occurrence in the aquatic environment. Knowledge about their influences on the microbial community, however, remains largely unknown. In the present study, Illumina high-throughput sequencing of 16S ribosomal DNA was applied to explore the changes in the dynamic and composition of the bacterial community upon exposure to perfluorooctanoic acid (PFOA) at different concentrations, i.e. 0.45 µg L-1, 130 µg L-1 and 5.0 mg L-1. Principal component analysis (PCA) revealed variations of 57.2% for Principal Component 1 and 16.0% for Principal Component 2 of the total community. This clearly demonstrated changes in the bacterial community structure between the controls and PFOA-amended water samples. At the phylum level, the predominant bacteria in the original pond water included Proteobacteria (64.47%), Armatimonadetes (11.87%), Actinobacteria (10.81%), Bacteroidetes (6.36%), Chloroflexi (1.44%), Verrucomicrobia (0.61%) and Firmicutes (0.14%). The relative abundance of Actinobacteria, Bacteroidetes, and Verrucomicrobia decreased 26.5-38.8%, 40.5-70.7%, and 47.4-87.5%, respectively, upon PFOA exposure. By contrast, PFOA led to an obvious increase of Proteobacteria, by 12.5-18.6% and Chloroflexi by 19.1-74.4%. Results from this study provided the needed evidence that PFAS at high concentrations could affect the microbial community in a freshwater ecosystem. Principle Component Analysis (PCA) results suggest clear distinctions of bacterial community structure between the original pond water and the water samples spiked with PFOA based on pyrosequencing of 16S rRNA gene